Dimensions of supply risks in the supply of water: A case of Zet district municipality - Mbhele, Thokozani Patmond; Khuzwayo, Sebenzile (International Journal of Innovative Research and Scientific Studies, 2023)
The purpose of the study is to ascertain water supply risks in a district municipality, in South Africa. It aims to strike a balance between the risk of water supply and demand within the Zet District Municipality’s capacity for integrated water service delivery. Inductive thematic analysis and in-depth interviews with district administrators were used to collect qualitative data as part of an exploratory case study design. The findings from the interpretive philosophy reveal that district municipalities lack the capacity to deliver water services due to a variety of supply chain risks and augmenting water demand from the community. Due to the detrimental effects of water shortages on livelihoods, the district’s supply risk management capacities need to be strengthened. The supply chain operations should mitigate supply risks not just in water supply, but in service delivery as a whole by striking a balance between water demand and supply to address supply risks. The supply risks that are recognised should take into account data sharing, supplier agility, adaptability, dependability, and infrastructure quality. The force field analysis created a platform to identify the forces that provide a change in the water supply.